The value of women's body signs in Maman Suherman's novel Re dan Perempuan: A postmodernist study - Suarni Syam Saguni (Lililacs Journal, 2024)
This study aims to analyze and discover the value of body signs in Maman Suherman's novel titled “Re dan Perempuan (2021)” through a postmodernism lens. This qualitative research aims to describe the meaning behind the meaning, as a phenomenon regarding the value of women's body signs in Maman Suherman's novels based on Jean Baudrillard's postmodernism theory. The results show the depiction of sexual behavior as a phenomenon in urban society. This behavior is part of the libido system where individuals engage in passive, weak, and powerless activities, even towards their own bodies. Essentially, in the postmodernism era, the value of these body signs is the forms of bodies driven by subjects, whether capitalism or patriarchy, that have rooted in certain societies.